PEMBENIHAN DAN AKLIMATISASI PADA SISTEM ANAEROBIK - indriyati, Indriyati (BPPT)
Seeding in Fixed Bed anaerobic reactor are infl uenced by several condition such as the growth rate total population of microbial, bacterial adaption to infl uent and the retention of biomass in reactor. The aim of this observation is to fi nd out the seeding and acclimation process in anaerobic process by using plastic as support material. Seeding and acclimatization process run smoothly can be seen from the increasing of infl uent or substrate and following by the increasing degradation of soluble COD, beside that the decreasing of VSS concentration indicates that microorganism are all ready fi x in support material, therefore reactor can be operated continuously and the acclimatization process can be stopped.Keywords : anaerobic seeding, acclimation anaerobic process